Population fluctuation of Diaphorina citri (Hemiptera: Liviidae) in Persian lime (Citrus latifolia), in Huimanguillo Tabasco, Mexico - García Garduza, Diógenes; Sánchez Soto, Saúl; Romero Nápoles, Jesús; Pérez Flores, Julián (Revista Colombiana de Entomología, 2013)
Diaphorina citri is the vector of Huanglongbing disease, which is currently in 12 of 23 citrus producing states in Mexico, including Tabasco, where there are 15,406 ha of these crops. The aim of this study was to determine the population dynamics of D. citri and its relation with the abundance of vegetative shoots, temperature and precipitation in Huimanguillo, Tabasco. The work was done by sampling fortnightly from September 2010 to August 2011 in a plantation of Persian lime (Citrus latifolia Tanaka) of 1 ha. Population dynamics of eggs and nymphs was determined by collecting vegetative shoots, and adult dynamics by capturing them in yellow sticky traps. The highest incidence of D. citri was between March and June, coinciding with the abundance of vegetative shoots and high temperature. The abundance of eggs and nymphs showed high correlation with that of vegetative shoots, moderate correlation with temperature, and negative correlation with rainfall. The incidence of adults exhibited a moderately correlation with temperature and a low correlation with abundance of vegetative shoots and precipitation.